Production and characterization of hydrophilic conjugated linoleic acid with improved oxidative stability using sunflower oil - Koohikamali, Sara (2013)
Conjugated linoleic acids (CLAs) as isomers of linoleic acid (LA) with two conjugated double bonds are regarded as functional lipids. CLA is commercially produced by alkali isomerization of LA rich oils (e.g., sunflower and safflower oils). However, the water insolubility and oxidative instability of commercial CLA are barriers which limit the applications of CLA for fortification of aqueous based foods. The main target of this research was to produce a hydrophilic derivative of CLA with an improved oxidative stability. In order to achieve this goal, sunflower oil was subjected to the transesterification. The optimum conditions resulting in a maximum yield (100 %) were at reaction time of 60 min, 6.5:1 molar ratio of methanol to oil and 0.5 % sodium methoxide (NaOCH3). The fatty acid methyl esters (FAMEs) were mainly the linoleic acid methyl esters (LAMEs) which then proceeded to the isomerization. An optimum point of 5 % NaOCH3, 1.06 % polyethylene glycol and 140 °C reaction temperature lead to an isomerization degree of 96.6 % and 72.90 % of the total conjugated linoleic acid methyl esters (CLAMEs). The CLA obtained from the purification of the hydrolyzed CLAMEs soap was then reacted with both Lysine (Lys) and Arginine (Arg). The formation of Lys-CLA and Arg-CLA was confirmed by FT-IR spectroscopy at 1650 and 1550 cm-1. The measurement of the peroxide values (PVs) of the samples as an indicator of the oxidative stability showed that the PVs of the Lys-CLA and Arg-CLA only increased by 1.4 and 1.5-fold, respectively, whereas the PVs of the CLA increased by 16-fold (12 h of storage at 60 °C). Furthermore, the mean of the Lys-CLA PVs (0.32) was significantly lower (p < 0.05) compared to the Arg-CLA (0.49). The Lys-CLA, Arg-CLA, Lys, Arg and CLA showed some antioxidative potential in the DPPH and ABTS assays. Lys-CLA with the smallest half maximal inhibitory concentration (IC50) exhibiting the greatest antioxidant activity (p 0.05) among the samples. A visual inspection test on the stability of the Lys-CLA and Arg-CLA solutions indicated that the stability of Arg-CLA in neutral water is greater than that of Lys- CLA at concentrations > 0.2 % (two weeks of storage at 25 ± 1 °C). Moreover, the pH, concentration and type of salt (NaCl and CaCl2) and Lys-CLA concentrations as well as the interaction between pH and the salt concentration significantly affected the solubility of the Lys-CLA (p < 0.05). The highest water solubility was at pH 2 and when the concentration of Lys-CLA was ≤ 1.75% with no added salt (0 mM). In contrast, the solubility of Lys-CLA was the least at pH 5-7, 200 mM salt concentration and 2.50 % Lys-CLA concentration. This study confirmed that Lys can be a substitute for Arg in Arg-CLA as suggested in earlier literature due to the inherent polarity and antioxidative potential. Thus, the incorporation of Lys into the CLA molecule can improve the oxidative stability, antioxidant capacity and water miscibility of CLA, and expand the applications of CLA into the enrichment of the nutraceutical beverages.